PENGARUH PERSONAL SELLING DAN PENGEMBANGAN PRODUK TERHADAP VOLUME PENJUALAN PT. INFINITI INTERNASIONAL LOGISTIC MEDAN - Hery Hery; Thomas Sumarsan Goh; Errie Margery (STIE-PMCI, 2019)
Abstract. Sales volume is one of the determining factors that greatly influences the achievement of net income, while profit or profit is an important means for the survival of a company, therefore the company must strive to create profitable sales volumes. The higher the sales volume, the profits obtained increase, thus the company will be able to survive, grow and develop further, and be strong in overcoming the influence of environmental factors that are constantly changing.The method used in this study is quantitative. The population and sample of this study are customers of PT. Infiniti International which amounted to 81 respondents. Questionnaire processing is measured by a Likert scale. The data analysis model used is multiple linear regression analysis and classical assumption test.The results of the study show that partially and simultaneously personal selling and product development have a significant positive effect on sales volume at PT. Infiniti International Logistics.Â Â Keywords: Personal Selling, Product Development, Sales Volume.Â